Technological acquisitions and the innovation performance of acquiring firms: a longitudinal study - Ahuja, Gautam; Katila, Riitta (Strategic Management Journal, 2001)
Abstract This paper examines the impact of acquisitions on the subsequent innovation performance of acquiring firms in the chemicals industry. We distinguish between technological acquisitions, acquisitions in which technology is a component of the acquired firm's assets, and nontechnological acquisitions: acquisitions that do not involve a technological component. We develop a framework relating acquisitions to firm innovation performance and develop a set of measures for quantifying the technological inputs a firm obtains through acquisitions. We find that within technological acquisitions absolute size of the acquired knowledge base enhances innovation performance, while relative size of the acquired knowledge base reduces innovation output. The relatedness of acquired and acquiring knowledge bases has a nonlinear impact on innovation output. Nontechnological acquisitions do not have a significant effect on subsequent innovation output. Copyright © 2001 John Wiley & Sons, Ltd.